Tactile Sensing for Minimally Invasive Surgery: Conventional Methods and Potential Emerging Tactile Technologies - Othman, Wael; Lai, Zhi-Han A.; Abril, Carlos; Barajas-Gamboa, Juan S.; Corcelles, Ricard; Kroh, Matthew; Qasaimeh, Mohammad A. (Frontiers in Robotics and AI, 2022)
As opposed to open surgery procedures, minimally invasive surgery (MIS) utilizes small skin incisions for the insertion of surgical instruments. MIS has numerous advantages such as; reduced postoperative pain, shorter hospital stay, faster recovery time, and reduced learning curve for surgical trainees. MIS comprises surgical approaches, including laparoscopic surgery, endoscopic surgery, and robotic-assisted surgery. Despite the advantages that MIS provides to patients and surgeons, it remains limited by the lost sense of touch due to the indirect contact with tissues under operation, especially in robotic-assisted surgery. Surgeons, without haptic feedback, could unintentionally apply excessive forces that may cause tissue damage. Therefore, incorporating tactile sensation into MIS tools has become an interesting research topic. Designing, fabricating, and integrating force sensors onto different locations on the surgical tools are currently under development by several companies and research groups. In this context, electrical force-sensing modality, including piezoelectric, resistive, and capacitive sensors, is the most conventionally considered approach to measure the grasping force, manipulation force, torque, and tissue compliance. For instance, piezoelectric sensors exhibit high sensitivity and accuracy, but the drawbacks of thermal sensitivity and the inability to detect static loads constrain their adoption in MIS tools. Optical-based tactile sensing is another conventional approach that facilitates electrically passive force-sensing compatible with magnetic resonance imaging. Estimations of applied loadings are calculated from the induced changes in the intensity, wavelength, or phase of light transmitted through optical fibers. Nonetheless, new emerging technologies are also evoking a high potential of contributions to the field of smart surgical tools. The recent development of flexible, highly-sensitive tactile microfluidic-based sensors has become an emerging field in tactile sensing, which contributed to wearable electronics and smart-skin applications. Another emerging technology is imaging-based tactile sensing that achieved superior multi-axial force measurements by implementing image sensors with high pixel densities and frame rates to track visual changes on a sensing surface. This article aims to review the literature on MIS tactile sensing technologies in terms of working principles, design requirements, and specifications. Moreover, this work highlights and discusses the promising potential of few emerging technologies towards establishing low-cost, high-performance MIS force sensing.